2019
DOI: 10.22543/7674.62.p224231
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in the treatment of chronic lung diseases

Abstract: Nanoparticles, although considered a topic of modern medicine, actually have an interesting history. Currently, advances in nanomedicine hold great promise as drug carrier systems for sustained release and targeted delivery of diverse therapeutic agents. Nanoparticles can be defined as complex drug carrier systems which incorporate and protect a certain drug or particle. Nanoparticles can be administered via different routes, such as intravenous injection, oral administration, or pulmonary inhalation. Even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…COPD is a disorder characterized by chronic incomplete reversible airway limitation (11)(12). During the chronic evolution of this disease, patients develop dyspnoea, fatigue, limited exercise capacity, symptoms that will lead to a vicious circle of sedentary lifestyle -deconditioning -muscular dysfunction (13,14) Muscle weakness is independent of airflow obstruction severity of and is a significant risk factor for falls in this population (15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…COPD is a disorder characterized by chronic incomplete reversible airway limitation (11)(12). During the chronic evolution of this disease, patients develop dyspnoea, fatigue, limited exercise capacity, symptoms that will lead to a vicious circle of sedentary lifestyle -deconditioning -muscular dysfunction (13,14) Muscle weakness is independent of airflow obstruction severity of and is a significant risk factor for falls in this population (15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress and inflammation play an important role in the pathogenesis of asthma. Growing evidence has indicated that nanoparticle-based anti-inflammation and antioxidant strategies are promising for the treatment of allergic airway inflammation and asthma (Fatani, 2014;Sahiner et al, 2018;Alexescu et al, 2019;. The anti-asthmatic effects of two organic nanoparticles, i.e., BRNPs and HPOX nanoparticles with intrinsic antioxidant activity were evaluated using a murine model of asthma (Yoo et al, 2013;Kim D. E. et al, 2017).…”
Section: Other Inflammatory Diseasesmentioning
confidence: 99%
“…COPD is a frequent comorbidity in patients with IPF and the rehabilitation programs have proven their efficacy. In these subjects, there were improvements in dyspnea, functional exercise-capacity (measured by 6MWT) and health-related quality of life (44,48). Despite the fact that the mechanism of exercise intolerance differs between COPD and IPF, the rehabilitation therapies approved for COPD patients are effective to achieve a suitable exercise capacity in patients with IPF.…”
Section: Copdmentioning
confidence: 99%